PTFE-coated needle punched felt filter material and preparation method thereof
Patent Information
- Application Number
- CN202611215875.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-12
AI Technical Summary
[0003]在已有的覆膜针刺毡滤料中,滤料通常以除尘为单一功能,难以在同一滤料上兼顾对氮氧化物等污染物的净化
[0039]本发明在膨体聚四氟乙烯微孔膜的迎尘面设置离散分布的功能颗粒区,并使功能颗粒经含硅结合相固着于膜孔孔缘及节点凸起处而不连成连续封闭膜层,因而在向迎尘面引入功能组分的同时使膜孔的贯通孔喉保持开放。由于气流可经由保持开放的孔喉穿过膜层,本发明在提高功能负载的同时仍维持较低的过滤阻力,从而化解了功能负载量与过滤阻力之间的相互制约。在制备过程中,本发明以膜面活化、表面张力调控、负压抽吸与红外预干燥相配合,使功能颗粒限域固着于孔缘而不灌满孔喉,并以保留面载量的控制关系对涂布加以调节,因而所得功能颗粒区的离散形貌可控且便于复现。在该结构的作用下,迎尘面以表面过滤方式拦截亚微米粉尘,残尘较少,脉冲清灰后过滤阻力较易恢复,使滤料兼具较高的过滤效率与较低的运行阻力。
Smart Images

Figure CN122702227B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dust-laden gas purification technology, specifically relating to a PTFE-coated needle-punched felt filter bag and its preparation method. Background Technology
[0002] This invention relates to the field of dust-laden gas purification, and more particularly to membrane-coated needle-punched felt filter media used in baghouse dust collectors and its preparation method. Baghouse dust collection is a common method for industrial flue gas dust removal, which uses filter media to intercept dust in the flue gas and relies on pulse cleaning to maintain operation. By compositing an expanded polytetrafluoroethylene (ePTFE) microporous membrane onto the dust-facing side of the filter media, dust can be mainly intercepted on the membrane surface, facilitating cleaning. Therefore, membrane-coated needle-punched felt filter media is used in industrial dust removal. With increasingly stringent requirements for flue gas treatment, industrial flue gas often contains nitrogen oxides, sulfur dioxide, hydrogen chloride, and hydrogen fluoride, among other acidic components, in addition to dust. Furthermore, some dust particles are sticky and easily accumulate static electricity. Therefore, there is a need for filter media that can simultaneously remove dust and simultaneously purify multiple pollutants, as well as ensure long-term stable operation.
[0003] In existing membrane-coated needle-punched felt filter media, the filter media typically functions solely for dust removal, making it difficult to simultaneously purify pollutants such as nitrogen oxides on the same filter media. When attempting to load catalytic or functional components onto the filter media, existing methods often employ impregnation or full coating to form a continuous coating on the membrane surface. However, this continuous coating can close membrane pores and increase filtration resistance. Therefore, the loading capacity of functional components and filtration resistance are mutually restrictive, making it difficult to maintain low operating resistance while increasing functional loading. Existing methods also often use organic adhesives to fix functional components. Organic adhesives are prone to aging, pulverizing, and detachment in medium- and high-temperature and acidic atmospheres, making it difficult to maintain strong fixation of functional components and the bonding between the membrane and the substrate during long-term operation. Methods using carbon black as an antistatic component have been developed, but in oxygen-containing acidic high-temperature atmospheres, carbon black is easily oxidized and ablated, losing its conductivity, making it difficult to maintain the antistatic effect long-term. Manganese-cerium catalysts used for low-temperature denitrification are easily deactivated in sulfur-containing and water-containing atmospheres due to the deposition of ammonium sulfate at active sites, making it difficult to maintain catalytic activity over a long period. For sticky dust, the existing filter media's dust-repellent surface lacks sufficient repellency, allowing sticky dust to easily adhere and cause bag clogging, making it difficult to restore filtration resistance after cleaning. Furthermore, if the coating and setting processes are carried out at temperatures close to or exceeding the melting point of polytetrafluoroethylene (PTFE), the membrane's microporous structure is prone to collapse, reducing air permeability. Pinholes formed by stitching can also easily become leakage channels for dust-laden gas. Moreover, existing loading processes lack quantitative control over the coating amount, making it difficult to reproduce the morphology and loading of functional areas.
[0004] As can be seen from the above, existing membrane-coated needle-punched felt filter media still have shortcomings in terms of multi-functional integration, firm fixation of functional components, durability of antistatic and catalytic components, anti-clogging and dust removal, maintenance of pore structure, and controllability of loading process. Therefore, it is necessary to design a membrane-coated needle-punched felt filter media dust collector bag that can efficiently remove dust at low filtration resistance, and can also take into account catalytic denitrification, antistatic, anti-clogging and auxiliary deacidification, and has firm fixation and stable pore structure, as well as its preparation method. Summary of the Invention
[0005] To address the problems existing in the background art, the present invention provides a PTFE-coated needle-punched felt filter bag, wherein the filter bag comprises a bag-shaped hollow filter body surrounded by PTFE-coated needle-punched felt filter material; wherein:
[0006] The PTFE-coated needle-punched felt filter media includes polytetrafluoroethylene needle-punched felt and expanded polytetrafluoroethylene microporous membrane disposed on the dust-facing side of the polytetrafluoroethylene needle-punched felt. The side of the expanded polytetrafluoroethylene microporous membrane facing away from the polytetrafluoroethylene needle-punched felt is the dust-facing side. The other side of the expanded polytetrafluoroethylene microporous membrane is embedded in the gaps between the surface fibers of the polytetrafluoroethylene needle-punched felt to form a membrane-fiber interlocking interface. The dust-facing side has discretely distributed functional particle regions. The functional particle regions are fixed to the membrane pore edges and node protrusions of the expanded polytetrafluoroethylene microporous membrane by a silicon-containing bonding phase. The functional particle regions do not form a continuous closed membrane layer, and the through pore throats of the expanded polytetrafluoroethylene microporous membrane remain open.
[0007] The functional particle zone is formed by drying and heat setting of a multifunctional liquid. Based on the mass fraction of non-volatile components in the multifunctional liquid, the multifunctional liquid includes 5-12 parts of tungsten-modified manganese-cerium composite oxide, 0.5-3 parts of antimony-doped tin dioxide, 0.5-3 parts of γ-glycidyl etheroxypropyltrimethoxysilane, and 0.2-1.5 parts of 1H,1H,2H,2H-perfluorodecyltriethoxysilane. The γ-glycidyl etheroxypropyltrimethoxysilane is hydrolyzed and condensed to form a silicon-containing phase, and the 1H,1H,2H,2H-perfluorodecyltriethoxysilane is hydrolyzed and condensed to form a fluorinated hydrophobic phase located on the dust-facing surface of the functional particle zone.
[0008] In a preferred embodiment, the tungsten-modified manganese-cerium composite oxide has a molar ratio of manganese, cerium, and tungsten of (5-7):(3-5):(0.5-1.5) based on the molar number of metal elements; the median particle size of the tungsten-modified manganese-cerium composite oxide is 0.05-0.20 μm, and the particle size corresponding to 90% of the cumulative volume distribution is not greater than 0.30 μm.
[0009] In a preferred embodiment, the antimony in the antimony-doped tin dioxide has a mass fraction of 8%–12% and a number-average primary particle size of 20–30 nm; the areal density of the polytetrafluoroethylene needle-punched felt is 500–800 g / m³. 2The expanded polytetrafluoroethylene microporous membrane has an average pore size of 0.2–0.5 μm, a porosity of 80%–90%, and an areal density of 5–15 g / m³. 2 .
[0010] In a preferred embodiment, the functional particle region further includes 0.2 to 1 part by weight of perfluorosulfonic acid resin, and 1 to 3 parts by weight of magnesium aluminum hydrotalcite and / or magnesium aluminum composite oxide.
[0011] This invention also provides a method for preparing PTFE-coated needle-punched felt filter bags, comprising the following steps:
[0012] S1. The pre-made polytetrafluoroethylene needle-punched felt is dried and subjected to tension constraint thermal stabilization treatment to obtain pre-stabilized polytetrafluoroethylene needle-punched felt.
[0013] S2. The dust-facing surface of the expanded polytetrafluoroethylene microporous membrane is activated by atmospheric pressure dielectric barrier discharge plasma to obtain a surface-activated expanded polytetrafluoroethylene microporous membrane.
[0014] S3. A multifunctional liquid containing tungsten-modified manganese-cerium composite oxide, antimony-doped tin dioxide, γ-glycidyl etheroxypropyltrimethoxysilane and 1H,1H,2H,2H-perfluorodecyltriethoxysilane is coated onto the dust-facing surface activated in step S2. A negative pressure is applied to the back of the expanded polytetrafluoroethylene microporous membrane to cause the solid particles in the multifunctional liquid to adhere to the pore edges and node protrusions of the membrane pores, forming discretely distributed functional particle regions. The functional particle regions do not form a continuous closed membrane layer, and the through-hole throats of the expanded polytetrafluoroethylene microporous membrane remain open.
[0015] S4. The coated expanded polytetrafluoroethylene microporous membrane is pre-dried by infrared radiation.
[0016] S5. The expanded polytetrafluoroethylene microporous membrane treated in step S4 is stacked with the pre-stabilized polytetrafluoroethylene needle-punched felt on its uncoated side and hot-pressed to form a membrane-fiber interlocking interface, with the dust-facing side coated with the functional particle area facing outward.
[0017] S6. The hot-pressed filter material is subjected to gradient heat setting to obtain PTFE membrane needle-punched felt filter material;
[0018] S7. Perform pulsed airflow pre-purging treatment on the PTFE-coated needle-punched felt filter material to remove weakly attached particles in the functional particle area;
[0019] S8. The filter material treated in step S7 is sewn together to form a bag-shaped hollow filter body, thus obtaining the PTFE-coated needle-punched felt filter material dust collector bag.
[0020] Furthermore, step S1 includes:
[0021] S11. After degreasing and dust removal, the pre-made polytetrafluoroethylene needle-punched felt is dried at 100-120℃ to constant weight.
[0022] S12. The dried polytetrafluoroethylene needle-punched felt is heat-stabilized at 200-240℃ for 5-20 minutes under tension constraint to obtain pre-stabilized polytetrafluoroethylene needle-punched felt.
[0023] Step S2 includes:
[0024] S21. Position the dust-facing side of the expanded polytetrafluoroethylene microporous membrane directly against the dielectric barrier discharge electrode.
[0025] S22, at atmospheric pressure with an energy density of 0.5–3 W·min / cm³ 2 The dust-facing surface is activated by dielectric barrier discharge plasma to obtain a surface-activated expanded polytetrafluoroethylene microporous membrane.
[0026] Furthermore, the preparation of the multifunctional liquid in step S3 includes:
[0027] S31. Tungsten-modified manganese-cerium composite oxide with a median volumetric particle size of 0.05–0.20 μm and a particle size not greater than 0.30 μm corresponding to 90% volumetric cumulative distribution, antimony-doped tin dioxide with a number-average primary particle size of 20–30 nm, hydrolysate of γ-glycidyl etheroxypropyltrimethoxysilane, and ethanol hydrolysate of 1H,1H,2H,2H-perfluorodecyltriethoxysilane are added to a mixed solvent of deionized water and isopropanol at a volume ratio of 6:4. The mixture is ultrasonically dispersed for 30–60 min, and then a fluorocarbon surfactant is added to adjust the surface tension of the multifunctional solution to 18–22 mN / m. The multifunctional solution is dried at 105 °C to constant weight and the non-volatile solids content is measured to be 0.04–0.10 g / mL. Perfluorosulfonic acid resin and magnesium aluminum hydrotalcite and / or magnesium aluminum composite oxide are added to the mixed solvent.
[0028] Furthermore, the coating and negative pressure suction in step S3 include:
[0029] S32. The multifunctional liquid is coated onto the dust-facing surface activated in step S2 using slit extrusion coating, and a negative pressure of -2 to -8 kPa is applied to the back of the expanded polytetrafluoroethylene microporous membrane to draw in solid particles in the multifunctional liquid, so that the solid particles in the liquid are fixed at the pore edges and node protrusions of the membrane pores to form discretely distributed functional particle regions, while the through pore throats of the expanded polytetrafluoroethylene microporous membrane remain open.
[0030] S33. During the coating process in step S32, adjust the remaining surface load after drying according to the following formula:
[0031] ;
[0032] In the formula, To retain surface load after drying; The content of non-volatile solids in the multifunctional liquid feed solution is measured after drying at 105°C to constant weight. The feed flow rate for the slit extrusion nozzle; The width of the expanded polytetrafluoroethylene microporous membrane; The linear speed of the conveyor belt of the expanded polytetrafluoroethylene microporous membrane; and by adjusting , , , The intensity of the negative pressure suction ensures that the projected area of the functional particle region on the dust-facing surface accounts for 5% to 35%, and the surface load retained after drying is 1 to 6 g / m². 2 .
[0033] Further, step S4 involves: pre-drying the coated expanded polytetrafluoroethylene microporous membrane using infrared technology at a membrane surface temperature of 80–140°C for 5–30 seconds; step S5 includes:
[0034] S51. The expanded polytetrafluoroethylene microporous membrane treated in step S4 is stacked with the pre-stabilized polytetrafluoroethylene needle-punched felt with its uncoated side facing outwards.
[0035] S52. Using a hot press roller, hot press for 5-30 seconds at 280-320℃ and 0.05-0.5MPa, the uncoated side of the expanded polytetrafluoroethylene microporous membrane is hot-pressed and deformed, and pressed into the gaps between the surface fibers of the polytetrafluoroethylene needle-punched felt to form a membrane-fiber interlocking interface.
[0036] Further, step S6 involves: subjecting the hot-pressed filter material to gradient heat setting at three temperature zones (200℃, 260℃, and 300℃) under tension constraint, with a total residence time of 1–5 minutes, to obtain PTFE-coated needle-punched felt filter material; step S8 also includes:
[0037] S82. Apply a fluorinated ethylene propylene copolymer dispersion along the suture pinhole area of the bag-shaped hollow filter body, and locally hot-press at 260-290°C to melt the fluorinated ethylene propylene copolymer and seal the pinhole.
[0038] The beneficial effects achieved by this invention are as follows:
[0039] This invention features discretely distributed functional particle regions on the dust-facing surface of an expanded polytetrafluoroethylene (ePTFE) microporous membrane. These functional particles are fixed to the membrane pore edges and node protrusions via a silicon-containing binding phase, preventing them from forming a continuous, closed membrane layer. This allows for the introduction of functional components to the dust-facing surface while maintaining the open pore throats. Since airflow can pass through the membrane layer via these open throats, this invention increases the functional loading while maintaining low filtration resistance, thus resolving the conflict between functional loading and filtration resistance. During preparation, this invention combines membrane activation, surface tension control, negative pressure suction, and infrared pre-drying to confine and fix the functional particles to the pore edges without filling the throats. The coating is adjusted by controlling the surface loading, resulting in a controllable and easily reproducible discrete morphology of the functional particle regions. Under this structure, the dust-facing surface intercepts submicron dust through surface filtration, resulting in less residual dust. Filtration resistance is easily recovered after pulse cleaning, giving the filter media both high filtration efficiency and low operating resistance.
[0040] This invention introduces tungsten-modified manganese-cerium composite oxide into the functional particle region. Utilizing the multivalent state transformation of manganese and cerium and the lattice oxygen vacancies, it provides active sites for the catalytic reduction of nitrogen oxides, thereby enabling the filter media to catalytically remove nitrogen oxides from medium- and low-temperature flue gas while intercepting dust. Because tungsten provides acidic sites on the catalyst surface and inhibits the deposition of ammonium sulfate on the active sites, this invention maintains catalytic activity in sulfur- and water-containing atmospheres, exhibiting superior sulfur and water resistance compared to non-tungsten-based materials. This invention uses antimony-doped tin dioxide as an antistatic component, leveraging its inorganic semiconductor properties to dissipate accumulated electrostatic charges on the dust-collecting surface. Furthermore, its resistance to oxidation and ablation in oxygen-containing acidic atmospheres ensures long-term antistatic effects. This invention also imparts a lower surface energy to the dust-collecting surface with a fluorine-containing hydrophobic phase, reducing the adhesion of sticky dust and facilitating dust removal. Magnesium-aluminum hydrotalcite or its heat-treated magnesium-aluminum composite oxide further assists in the capture of acidic components. Therefore, this invention integrates dust removal, catalytic denitrification, antistatic properties, anti-clogging, and auxiliary deacidification into a single unit, with each function coexisting without degrading the others.
[0041] This invention uses a silicon-containing binder phase instead of organic adhesives to fix functional particles. Because the silicon-containing binder phase is an inorganic network containing silicon-oxygen bonds, it is not easily aged or degraded in medium-high temperatures and acidic atmospheres. Therefore, the functional particles remain firmly fixed during long-term operation, and weakly attached particles are not easily detached after pre-purging. This invention performs plasma activation on the membrane surface before coating, forming a stable bond between the membrane surface and the silicon-containing binder phase, thus further improving the firmness of functional particle fixation and the reliability of the membrane-substrate bond. This invention causes one side of the membrane to undergo hot-press deformation under hot pressing, pressing it into the gaps between the surface fibers of the needle-punched felt to form a membrane-fiber interlocking interface. Because this bond does not rely on organic adhesives, it avoids the aging, powdering, and detachment of the adhesive layer in acidic atmospheres, ensuring the stability of the membrane-felt bond under medium-high temperature and acidic conditions. Since the temperatures of hot pressing and gradient heat setting are both controlled below the melting point of polytetrafluoroethylene, the microporous structure of the membrane is preserved during the bonding and setting process without collapsing. Therefore, the filter material has both strong interlayer bonding and stable pore structure.
[0042] This invention utilizes a slit extrusion coating technique combined with controlled surface loading, allowing the coating amount to be determined by adjustable parameters such as feed flow rate and conveyor speed. This facilitates control over the coverage and loading of functional particle zones, resulting in a stable and reproducible process, making the technical solution easy to implement. After stitching, this invention applies a fluorinated ethylene-propylene copolymer with a melting point lower than polytetrafluoroethylene (PTFE) along the stitching pinhole area and locally melts and seals the pinholes. Because the sealing temperature is below the membrane's melting point, the pinholes are sealed without damage to the microporous membrane, thus reducing leakage of dust-laden gas through the stitching pinholes. In summary, the dust collector bag obtained by this invention maintains low filtration resistance while achieving high filtration efficiency, and also possesses properties such as catalytic denitrification, antistatic properties, anti-clogging, auxiliary deacidification, and robust durability. It can operate stably for extended periods under medium-to-high temperature conditions with acidic components in the dust-laden flue gas, thereby meeting the needs for synergistic purification of multiple pollutants. Attached Figure Description
[0043] Figure 1 This is a comparison chart of the initial filtration pressure difference and air permeability retention rate of Examples 1 to 4 and Comparative Examples 1, 2, 7, and 8.
[0044] Figure 2 The graphs show a comparison of the nitrogen oxide removal performance of Examples 1, 3, 4 and Comparative Example 3. (a) is a graph showing the removal rate as a function of temperature, and (b) is a graph showing the removal rate as a function of time after the introduction of sulfur dioxide and water vapor.
[0045] Figure 3The graphs show the antistatic durability of Examples 1, 3 and 4 and the anti-clogging performance of Examples 1, 5 and 1. (a) is a graph showing the change of surface resistance of Examples 1, 3 and 4 with oxidation aging time, and (b) is a graph showing the change of filtration pressure difference increment of Examples 1, 5 and 1 with operating time under high humidity and ammonium bisulfate conditions.
[0046] Figure 4 The graphs are comparative graphs verifying the interface firmness of Example 1, Comparative Example 2 and Comparative Example 6 and the formula for retaining surface load of Examples 1 to 4. Among them, (a) is a bar graph of the initial peel strength and peel strength after acid heat aging of Example 1, Comparative Example 2 and Comparative Example 6, and a scatter plot of the functional point detachment rate. (b) is a scatter plot comparing the calculated and measured values of the retaining surface load of Examples 1 to 4.
[0047] Figure 5 This is a front half-sectional view of the overall structure of the polytetrafluoroethylene-coated needle-punched felt filter bag of the present invention.
[0048] Figure 6 yes Figure 5 An enlarged sectional view of the layered cross-section of the filter media wall shown at point A.
[0049] Figure 7 yes Figure 6 An enlarged cross-sectional view of the microstructure of the functional particle region on the dust-facing surface, shown at point B.
[0050] In the picture:
[0051] 1. Dust collector bag; 2. Polytetrafluoroethylene needle-punched felt; 3. Expanded polytetrafluoroethylene microporous membrane; 4. Functional particle zone; 5. Dust-facing surface; 6. Through-hole throat. Detailed Implementation
[0052] The following provides a detailed description of a polytetrafluoroethylene (PTFE) coated needle-punched felt filter bag and its preparation method.
[0053] In the following description, polytetrafluoroethylene is abbreviated as PTFE; expanded polytetrafluoroethylene refers to polytetrafluoroethylene that has been biaxially stretched to form a microporous structure. Unless otherwise specified, all parts in this specification are parts by weight.
[0054] The dust collector bag 1 comprises a bag-shaped hollow filter body surrounded by polytetrafluoroethylene-coated needle-punched felt filter media. (Reference) Figures 5-7In a baghouse dust collector, the hollow bag filter receives dust-laden gas on its dust-facing surface 5. Dust is trapped on one side of the dust-facing surface 5, while clean gas passes through the filter material and is discharged. After a period of operation, a pulsed airflow is used to reverse-purge the dust-facing surface 5, causing the dust layer on the surface 5 to peel off and fall off, thereby maintaining a low operating pressure differential. The polytetrafluoroethylene (PTFE) coated needle-punched felt filter material includes PTFE needle-punched felt 2 and expanded PTFE microporous membrane 3 disposed on the dust-facing side of the PTFE needle-punched felt 2. PTFE needle-punched felt 2 is selected as the main load-bearing component because PTFE has good resistance to acidic components such as sulfuric acid mist, hydrogen chloride, and hydrogen fluoride, as well as humid and hot acidic condensates, and can withstand high operating temperatures, making it suitable for long-term use under medium- and high-temperature dust-laden gas conditions. The expanded polytetrafluoroethylene (ePTFE) microporous membrane 3 uses its microporous structure as a surface filtration layer, allowing dust to be primarily intercepted on the dust-receiving surface of the membrane without penetrating the filter media, thereby reducing residual dust and improving the stripping effect of pulse cleaning. Preferably, the areal density of the polytetrafluoroethylene needle-punched felt 2 is 500 g / m³. 2 Up to 800g / m 2 The expanded polytetrafluoroethylene microporous membrane 3 has an average pore size of 0.2 μm to 0.5 μm, a porosity of 80% to 90%, and an areal density of 5 g / m³. 2 Up to 15g / m 2 Controlling the average pore size of the membrane within the submicron range enables the membrane to effectively intercept submicron dust particles; maintaining a high porosity helps to retain air permeability while intercepting dust, thus maintaining low filtration resistance.
[0055] The side of the expanded polytetrafluoroethylene (ePTFE) microporous membrane 3 facing away from the polytetrafluoroethylene (PTFE) needle-punched felt 2 forms the dust-facing surface 5, while its opposite side combines with the surface fibers of the PTFE needle-punched felt 2 to form a membrane-fiber interlocking interface. This membrane-fiber interlocking interface refers to the interface formed when the other side of the membrane undergoes hot-pressing deformation under hot-pressing and is pressed into the gaps between the surface fibers of the PTFE needle-punched felt 2. Using this bonding method without the aid of organic adhesives avoids the aging, powdering, and detachment of the adhesive layer in medium- and high-temperature acidic gases, and prevents the volatile substances from the adhesive layer from contaminating the filter media, thus ensuring the stability of the membrane-felt bond under medium- and high-temperature acidic conditions.
[0056] A discretely distributed functional particle region 4 is provided on the dust-receiving surface 5. The functional particle region 4 refers to a particle aggregation region composed of discretely arranged functional particles that are not connected into a continuous closed membrane layer. The functional particle region 4 is fixed to the membrane pore edges and node protrusions of the expanded polytetrafluoroethylene microporous membrane 3 via a silicon-containing bonding phase. The proportion of the projected area of the functional particle region 4 on the dust-receiving surface 5 is statistically analyzed based on scanning electron microscopy images; the projected area proportion refers to the ratio of the projected area of the functional particle region 4 on the dust-receiving surface 5 to the area of the dust-receiving surface 5, preferably 5% to 35%. By confining the functional particles to the membrane pore edges and node protrusions and controlling the proportion of the projected area, the membrane pore throats 6 between adjacent functional particles remain open, allowing airflow to pass through the membrane layer via these open throats. This maintains low filtration resistance while introducing functional particles to the dust-receiving surface 5. Simultaneously, the airflow passing through the membrane layer must pass through the pore edge region where the functional particles are located, ensuring sufficient gas-solid contact, allowing a small number of functional particles to play their corresponding role. The design principle of confined fixation is to resolve the mutual constraint between the functional component load and the filtration resistance, so as to achieve a balance between high functional load and low operating resistance, and to avoid functional components forming a dense membrane layer that could cause pore blockage, cracking or detachment.
[0057] Functional particle zone 4 is formed by drying and heat setting of a multifunctional liquid, and its composition is based on the mass fraction of non-volatile components in the multifunctional liquid. The multifunctional liquid includes tungsten-modified manganese-cerium composite oxide, antimony-doped tin dioxide, γ-glycidyl etheroxypropyltrimethoxysilane, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane. Preferably, the tungsten-modified manganese-cerium composite oxide is 5 to 12 parts, the antimony-doped tin dioxide is 0.5 to 3 parts, the γ-glycidyl etheroxypropyltrimethoxysilane is 0.5 to 3 parts, and the 1H,1H,2H,2H-perfluorodecyltriethoxysilane is 0.2 to 1.5 parts. The composition is based on the mass fraction of non-volatile components in the liquid because the mass of silane changes after hydrolysis, condensation, drying, and heat setting; using the mass fraction as a measurement standard facilitates batching and reproducibility.
[0058] Tungsten-modified manganese-cerium composite oxide is a composite oxide with manganese, cerium, and tungsten as its metal components. Preferably, the molar ratios of manganese, cerium, and tungsten, based on the molar number of metal elements, are 5 to 7, 3 to 5, and 0.5 to 1.5, respectively. Valence state transitions can occur between the multiple valence states of manganese and cerium, forming oxygen vacancies in the crystal lattice. This promotes the generation of surface active oxygen species and the conversion of nitric oxide to nitrogen dioxide in the gas phase, thus promoting the reduction of nitrogen oxides. The introduction of tungsten provides acidic sites on the surface, inhibiting the deposition of ammonium sulfate on the active sites and improving the tolerance to sulfur dioxide and water vapor. Therefore, under medium- and low-temperature dusty gas conditions, the tungsten-modified manganese-cerium composite oxide on the dust-facing surface 5 can provide active sites for the catalytic reduction of nitrogen oxides, enabling the dust collector bag 1 to both filter dust and catalyze nitrogen oxides. To facilitate the adhesion of the tungsten-modified manganese-cerium composite oxide to the membrane pore edges without clogging the pore throats, its particle size is controlled. Preferably, the median volumetric particle size is 0.05 μm to 0.20 μm, and the particle size corresponding to 90% of the cumulative volume distribution is not greater than 0.30 μm; wherein, the median volumetric particle size refers to the particle size corresponding to 50% of the cumulative volume distribution, and the particle size corresponding to 90% of the cumulative volume distribution refers to the particle size corresponding to 90% of the cumulative volume distribution. Controlling the particle size to be smaller than the average pore size of the membrane, and using a silicon-containing binding phase for fixation, ensures that the particles adhere to the pore edges and do not pass through the pore throat with the gas flow. The tungsten-modified manganese-cerium composite oxide can be prepared by a citric acid complexation sol-gel method, in which manganese nitrate, cerium nitrate, and ammonium metatungstate are dissolved in deionized water in the above molar ratio, citric acid is added as a complexing agent, the mixture is stirred to form a sol, dried to form a gel, calcined in an air atmosphere, and then ground to the above particle size range. The preferred calcination temperature is 400℃ to 500℃.
[0059] Antimony-doped tin dioxide is an n-type semiconductor particle obtained by doping tin dioxide with antimony. Preferably, the antimony mass fraction is 8% to 12%, and the number-average primary particle size is 20 nm to 30 nm; where the number-average primary particle size refers to the primary particle size obtained by weighting the number of particles. Antimony-doped tin dioxide provides a conductive path on the dust-receiving surface 5, allowing the electrostatic charge accumulated on the dust-receiving surface 5 to be discharged, reducing the risk of discharge caused by electrostatic accumulation. Compared with carbon black-based conductive materials, antimony-doped tin dioxide is not easily oxidized and ablated in oxygen-containing oxidizing acidic gases, making it easier to maintain antistatic properties for a long time under dusty gas conditions. Controlling the antimony doping of tin dioxide to prevent it from forming a dense conductive layer on the dust-receiving surface 5 can avoid clogging of the pore throat while discharging static electricity.
[0060] In a multifunctional feed solution, γ-glycidoxypropyltrimethoxysilane undergoes hydrolysis and condensation to form a silicon-containing bound phase. This silicon-containing bound phase refers to a network-like bound phase containing silicon-oxygen bonds, formed by the hydrolysis and condensation of silane. The silanol group at one end of the silane condenses with the oxygen-containing groups generated upon activation of the membrane surface and the hydroxyl groups on the surface of the functional particles to form bonds. The epoxy groups at the other end cross-link and solidify, thereby constituting a network-like silicon-containing bound phase that fixes the functional particles at the membrane pore edges and node protrusions. Using a silicon-containing bound phase instead of organic adhesives allows the fixed phase to withstand medium-high temperatures and acidic gases, and reduces high-temperature volatiles. 1H,1H,2H,2H-perfluorodecyltriethoxysilane undergoes hydrolysis and condensation to form a fluorinated hydrophobic phase located on the dust-facing surface of functional particle region 4; this fluorinated hydrophobic phase refers to a low surface energy phase rich in perfluoroalkyl groups, formed by the hydrolysis and condensation of fluorinated silane. Its perfluoroalkyl groups are arranged towards the dust-facing side, giving the dust-facing surface a low surface energy and making it repellent to both water and oil. This reduces the adhesion of sticky materials such as ammonium bisulfate, chloride salts, oil mist, and tar to the dust-facing surface 5, making it easier for the pulse airflow to peel off the dust layer as a whole, and making it easier to restore the operating pressure difference after pulse cleaning.
[0061] The functional particle region 4 may further include perfluorosulfonic acid resin and magnesium aluminum hydrotalcite and / or magnesium aluminum composite oxide. Preferably, the perfluorosulfonic acid resin is 0.2 to 1 part, and the magnesium aluminum hydrotalcite and / or magnesium aluminum composite oxide is 1 to 3 parts. The perfluorosulfonic acid resin plays a role in dispersion stabilization and film formation assistance in the multifunctional feed solution, which helps the functional particles to be uniformly dispersed in the feed solution and form a moderately continuous fixed phase after drying. Magnesium aluminum hydrotalcite is a layered double hydroxide with the chemical formula Mg6Al2(OH). 16 CO3·4H2O. The alkaline sites and interlayer carbonate ions on the magnesium-aluminum hydrotalcite (MgA) layer can neutralize and capture acidic components such as hydrogen chloride, hydrogen fluoride, and sulfuric acid trioxide mist. The captured acidic components are discharged with the dust layer during pulse backflushing. After heat treatment, MgA can be partially transformed into magnesium-aluminum composite oxide, which is also alkaline and maintains its ability to capture acidic components. Therefore, the corresponding component in functional particle zone 4 can be MgA, magnesium-aluminum composite oxide, or a mixture of the two, so that the product retains its auxiliary capture effect on acidic components after subsequent heat treatment.
[0062] The preparation method of the dust collector bag 1 described above will be further explained below. The method includes steps S1 to S8.
[0063] Step S1 involves drying and tension-constrained heat stabilization of the pre-fabricated PTFE needle-punched felt 2 to obtain pre-stabilized PTFE needle-punched felt 2. Step S1 includes steps S11 and S12. The pre-fabricated PTFE needle-punched felt 2 refers to the needle-punched felt directly used in this method after being formed and needle-punched in the previous process. This method does not involve the formation and needle-punching of the needle-punched felt. In step S11, the pre-fabricated PTFE needle-punched felt 2 is dried to constant weight after degreasing and dust removal, preferably at a drying temperature of 100°C to 120°C, to remove oil, dust, and moisture, preventing them from affecting the bonding between the membrane and the felt and the fixation of functional particles in subsequent processing. In step S12, the dried polytetrafluoroethylene needle-punched felt 2 is subjected to heat stabilization treatment under tension constraint, preferably at a temperature of 200°C to 240°C for 5 to 20 minutes. This allows the needle-punched felt to release internal stress under constraint, reducing its thermal shrinkage during the subsequent heat setting in step S6, thereby preventing wrinkling or pore drift of the film surface due to felt shrinkage after lamination.
[0064] Step S2 involves activating the dust-facing surface 5 of the expanded polytetrafluoroethylene (ePTFE) microporous membrane 3 with atmospheric pressure dielectric barrier discharge plasma to obtain a surface-activated ePTFE microporous membrane 3. Step S2 includes steps S21 and S22. Dielectric barrier discharge refers to a low-temperature discharge generated under atmospheric pressure by placing an insulating dielectric between electrodes. In step S21, the dust-facing surface 5 of the ePTFE microporous membrane 3 is positioned facing the dielectric barrier discharge electrode. In step S22, the dust-facing surface 5 is activated with dielectric barrier discharge plasma at atmospheric pressure and a certain energy density, preferably 0.5 W·min / cm². 2 Up to 3 W·min / cm 2 The energy density refers to the product of the discharge power density and the processing time, reflecting the discharge energy received per unit area of the dust-facing surface 5. The expanded polytetrafluoroethylene microporous membrane 3 has low surface energy and strong chemical inertness, making it difficult for the silicon-containing binding phase to bond firmly with it when unactivated. After activation, oxygen-containing active groups are introduced into the dust-facing surface 5, increasing the surface energy and decreasing the contact angle with water, thus enabling a stable bond to form between the membrane surface and the silicon-containing binding phase, creating conditions for the firm fixation of functional particles.
[0065] Step S3 involves preparing a multifunctional liquid and coating it onto the dust-facing surface 5 activated in step S2. Simultaneously, negative pressure is applied to the back of the membrane to allow the solid particles in the liquid to adhere to the membrane pore edges and node protrusions, forming a discretely distributed functional particle region 4. Step S3 includes steps S31, S32, and S33.
[0066] In step S31, the tungsten-modified manganese-cerium composite oxide and antimony-doped tin dioxide, after particle size control, are added to a mixed solvent of deionized water and isopropanol, along with the hydrolysate of γ-glycidyl etheroxypropyltrimethoxysilane and the ethanol hydrolysate of 1H,1H,2H,2H-perfluorodecyltriethoxysilane. The mixture is preferably in a 6:4 volume ratio of deionized water to isopropanol. The particles are then ultrasonically dispersed to ensure uniform dispersion, preferably for 30 to 60 minutes. A fluorocarbon surfactant is then added to adjust the surface tension of the multifunctional solution to a low level, preferably 18 mN / m to 22 mN / m. Lowering the surface tension allows the solution to adequately wet and spread on the dust-facing surface 5 of the expanded polytetrafluoroethylene microporous membrane 3, enabling the solution to enter the membrane pore edges without filling the pore throats under subsequent negative pressure suction. The solid content of the multifunctional feed solution is measured as the content of non-volatile solids after drying to constant weight at 105°C, preferably from 0.04 g / mL to 0.10 g / mL. Defining the solid content as the content of non-volatile solids after drying to constant weight at 105°C is to eliminate the influence of solvents and volatile additives on the solid content measurement, thus providing a definite measurement standard for subsequent surface loading control. In preparing the functional particle region 4 containing additional components, perfluorosulfonic acid resin and magnesium aluminum hydrotalcite and / or magnesium aluminum composite oxide are also added to the mixed solvent in step S31.
[0067] In step S32, the multifunctional liquid is coated onto the dust-facing surface 5 activated in step S2 using slit extrusion coating. Simultaneously, negative pressure suction is applied to the back of the membrane, preferably with a gauge pressure of -2 kPa to -8 kPa. Slit extrusion coating allows for quantitative control of the feed rate, facilitating subsequent adjustment based on areal load. Applying negative pressure suction to the back of the membrane allows airflow to pass from the dust-facing surface 5 through the membrane pore throat 6 to the back of the membrane. The solid particles carried by the liquid are suspended by the airflow and retained at the membrane pore edges and node protrusions, while the throat 6 remains open due to the airflow, thereby forming a discretely distributed functional particle region 4.
[0068] In step S33, the coating process in step S32 is controlled according to the surface load remaining after drying. The surface load remaining after drying refers to the mass of non-volatile solids retained per unit area on the dust-facing surface 5 after drying. The volumetric flow rate of the liquid supplied to the dust-facing surface 5 by the slit extrusion head per unit time is... The mass flow rate of non-volatile solids in the supplied liquid is and The product; at the same time, the width is The expanded polytetrafluoroethylene microporous membrane 3 travels at a linear speed of belt. Moving forward, the coated dust-facing surface 5 has an area of... and The product of these factors; dividing the mass flow rate of non-volatile solids by the coated area yields the mass of non-volatile solids retained per unit area on the dust-facing surface 5, which is the surface load retained after drying. Therefore, the control relationship is as follows: ;
[0069] In the formula, To retain the surface loading (g / m²) after drying 2 ); The content of non-volatile solids (g / mL) is measured by drying the multifunctional liquid at 105℃ to constant weight. The feed flow rate (mL / min) for the slit extrusion nozzle; The width (m) of the expanded polytetrafluoroethylene microporous membrane 3. The linear velocity (m / min) of the expanded polytetrafluoroethylene (ePTFE) microporous membrane 3 is shown. From this relationship, it can be seen that, given a fixed solid content and width, the surface loading after drying can be quantitatively controlled by adjusting the feed flow rate and the linear velocity of the conveyor belt. This can be achieved by adjusting... , , , The intensity of the negative pressure suction ensures that the projected area ratio of the functional particle zone 4 to the dust-facing surface 5 and the surface load after drying are within the required range, preferably 5% to 35% and 1g / m². 2 Up to 6g / m 2 The areal load is controlled at a low level commensurate with the aforementioned projected area ratio, and negative pressure suction is used to maintain the pore throat open, so that the membrane layer after the introduction of functional particles remains breathable and is not sealed.
[0070] Step S4 involves infrared pre-drying the coated expanded polytetrafluoroethylene microporous membrane 3. The preferred membrane surface temperature is 80°C to 140°C, and the drying time is 5 to 30 seconds. Infrared pre-drying allows for rapid removal of solvent from the feed solution. During solvent removal, the solid particles carried by the feed solution remain near the membrane pore edges and nodal protrusions, reducing the tendency for particles to aggregate into the pore throats as they migrate with the liquid phase. This helps maintain the morphology of the discretely distributed functional particles and keeps the pore throats open.
[0071] Step S5 involves stacking and hot-pressing the expanded polytetrafluoroethylene (ePTFE) microporous membrane 3, treated in step S4, with the pre-stabilized polytetrafluoroethylene (PTFE) needle-punched felt 2 to form a membrane-fiber interlocking interface. Step S5 includes steps S51 and S52. In step S51, the ePTFE microporous membrane 3 is stacked with its uncoated side on the pre-stabilized PTFE needle-punched felt 2, with the dust-facing side 5 coated with the functional particle area 4 facing outwards, ensuring that the functional particle area 4 is located on the side receiving the dust-laden gas. In step S52, hot pressing is performed using a hot press roller, preferably at a temperature of 280°C to 320°C, a pressure of 0.05 MPa to 0.5 MPa, and a time of 5 to 30 seconds, causing the uncoated side of the membrane to deform under hot pressing and be pressed into the gaps between the surface fibers of the PTFE needle-punched felt 2, thus forming the membrane-fiber interlocking interface. Polytetrafluoroethylene has a melting point of approximately 327°C. By controlling the hot-pressing temperature below the melting point, the membrane deforms under heat and pressure and interlocks with the fibers without melting completely, thus achieving a strong bond while preserving the membrane's microporous structure.
[0072] Step S6 involves gradient heat setting of the hot-pressed filter media to obtain PTFE-coated needle-punched felt filter media. Preferably, the filter media is passed sequentially through three temperature zones with increasing temperatures under tension constraint. The preferred temperatures for these three zones are 200°C, 260°C, and 300°C, with a total residence time of 1 to 5 minutes. Gradient heat setting further condenses and solidifies the silicon-containing binding phase and the fluorinated hydrophobic phase, stabilizing the pore morphology of the membrane. The temperature of each zone is controlled below the melting point of PTFE, allowing for further release and matching of thermal shrinkage between the membrane and felt, while preventing membrane pore collapse due to overheating. This reduces membrane surface wrinkling and pore size drift caused by inconsistent thermal shrinkage after coating.
[0073] Step S7 involves pre-purging the PTFE-coated needle-punched felt filter media with pulsed airflow. Pulsed airflow is used to purge the dust-facing surface 5, removing weakly attached particles from the functional particle zone 4 and retaining the functional particles firmly bonded by the silicon-containing phase. This pre-purging is performed before the filter media is put into actual filtration, ensuring a more stable pressure differential during initial operation and reducing secondary dust emissions caused by the shedding of weakly attached particles in the early stages of operation.
[0074] Step S8 involves sewing the filter material treated in step S7 into a bag-shaped hollow filter body, resulting in a polytetrafluoroethylene (PTFE) membrane needle-punched felt filter bag 1. For areas with needle holes after sewing, step S8 further includes step S82. In step S82, a fluorinated ethylene propylene copolymer dispersion is applied along the needle hole area of the bag-shaped hollow filter body, and local hot-pressing is performed at a certain temperature to melt the fluorinated ethylene propylene copolymer and seal the needle holes. The preferred hot-pressing temperature is 260°C to 290°C. Fluorinated ethylene propylene copolymer (FEP) has a lower melting point than PTFE, so it can be melted and filled to seal the needle holes at a temperature below the membrane melting point. This seals the needle holes to reduce leakage of dust-laden gas through them without causing the expanded PTFE microporous membrane 3 to collapse due to heat. The sealing of the needle holes only occurs along the periphery of the needle holes and does not cover the main filtration area of the bag-shaped hollow filter body.
[0075] In summary, the dust collector bag 1 uses the functional particle region 4, which is discretely distributed and confined to the membrane pore edge, as its core. While maintaining low filtration resistance, it utilizes tungsten-modified manganese-cerium composite oxide to provide active sites for the catalytic reduction of nitrogen oxides, antimony-doped tin dioxide to dissipate static electricity, a fluorine-containing hydrophobic phase to reduce dust adhesion, magnesium-aluminum hydrotalcite or magnesium-aluminum composite oxide to assist in the capture of acidic components, and a silicon-containing binding phase to achieve adhesive-free fixation and resistance to medium-high temperatures and acidic gases. Its preparation method involves membrane surface activation, confined coating and negative pressure suction, infrared pre-drying, hot-pressing intercalation below the melting point of polytetrafluoroethylene, and gradient heat setting. This method firmly fixes the functional particles to the membrane pore edge without clogging the membrane pore throat 6, allowing those skilled in the art to implement this technical solution. The above description is a specific embodiment of the present invention. Equivalent substitutions and improvements made by those skilled in the art without departing from the concept of the present invention are all within the protection scope of the present invention.
[0076] Example 1: This example describes the preparation of a polytetrafluoroethylene (PTFE) membrane needle-punched felt filter bag 1 for purifying low-temperature dusty flue gas in coal-fired boilers. The surface density of S1 is 650 g / m³. 2 Pre-fabricated polytetrafluoroethylene needle-punched felt 2 was dried and subjected to tension-constrained thermal stabilization. S11 was dried to constant weight at 110℃, and S12 was thermally stabilized at 220℃ for 12 min under tension constraint. S2 had an average pore size of 0.3 μm, a porosity of 85%, and a surface density of 8 g / m³. 2 The expanded polytetrafluoroethylene microporous membrane 3 is activated by atmospheric pressure dielectric barrier discharge on its dust-facing surface 5. In step S21, the dust-facing surface 5 is aligned with the discharge electrode. In step S22, the discharge is activated at an energy density of 1.8 W·min / cm². 2Activation. In step S3, a multifunctional solution is prepared and coated. Step S31 consists of 8 parts of tungsten-modified manganese-cerium composite oxide (median volume particle size 0.12 μm, 90% volumetric particle size 0.25 μm), 1.5 parts of antimony-doped tin dioxide (number-average primary particle size 25 nm), 1.5 parts of hydrolysate of γ-glycidyl etheroxypropyltrimethoxysilane, and 0.8 parts of ethanol hydrolysate of 1H,1H,2H,2H-perfluorodecyltriethoxysilane. A mixture of deionized water and isopropanol in a volume ratio of 6:4 is then added. Mixed solvent, ultrasonically dispersed for 45 min, then fluorocarbon surfactant was added to adjust the surface tension to 20 mN / m. The solution was dried at 105℃ to constant weight, and the non-volatile solids content was measured to be 0.06 g / mL. The tungsten-modified manganese-cerium composite oxide had a manganese-cerium-tungsten molar ratio of 6:4:1 based on the molar number of metal elements. S32 was coated by slit extrusion and a -5 kPa negative pressure was applied to the back of the membrane to fix the solid particles to the membrane pore edges and node protrusions to form discrete functional particle regions 4. S33 was prepared according to... Adjust the fabric width to 1.0m, the conveyor belt speed to 3m / min, and the feed flow rate to 175mL / min. After drying, retain approximately 3.5g / m² of surface load. 2 The projected area accounts for approximately 20%. S4 involves infrared pre-drying at 110℃ for 15 seconds. In S5, S51 overlaps the uncoated side of the film with the pre-stabilized needle-punched felt, ensuring the dust-facing side (5) faces outwards. S52 uses a hot-press roller at 300℃ and 0.2MPa for 15 seconds to form a film-fiber interlocking interface. S6 involves gradient heat setting at three temperature zones (200℃, 260℃, and 300℃) for 3 minutes under tension constraint. S7 uses pulsed airflow to pre-purge and remove weakly adhering particles. S8 involves sewing and bag making. S82 applies a fluorinated ethylene propylene copolymer dispersion along the sewing needle hole area and locally hot-presses the holes at 275℃.
[0077] Example 2: The difference from Example 1 is that the lower limits of each parameter are used: 5 parts of tungsten-modified manganese-cerium composite oxide, 0.5 parts of antimony-doped tin dioxide, 0.5 parts of hydrolysate of γ-glycidyl etheroxypropyltrimethoxysilane, 0.2 parts of ethanol hydrolysate of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, a manganese-cerium-tungsten molar ratio of 5:5:0.5, and an S22 energy density of 0.5 W·min / cm³. 2 S31 surface tension 22 mN / m, S32 negative pressure -2 kPa, S33 ensures that the surface loading after drying is approximately 1.0 g / m³. 2 The hot pressing temperature of S52 is 280℃, and the rest is the same as in Example 1.
[0078] Example 3: The difference from Example 1 is that the upper limits of each parameter are used. The composition is: 12 parts tungsten-modified manganese-cerium composite oxide, 3 parts antimony-doped tin dioxide, 3 parts hydrolysate of γ-glycidyl etheroxypropyltrimethoxysilane, 1.5 parts ethanol hydrolysate of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, a manganese-cerium-tungsten molar ratio of 7:3:1.5, and an S22 energy density of 3 W·min / cm³. 2 S31 surface tension 18 mN / m, S32 negative pressure -8 kPa, S33 ensures that the surface loading after drying is approximately 6.0 g / m³. 2 The projected area accounts for approximately 34%, the S52 hot pressing temperature is 320℃, and the rest is the same as in Example 1.
[0079] Example 4: The difference from Example 1 is that in S31, 0.5 parts of perfluorosulfonic acid resin and Mg6Al2(OH) are added to the mixed solvent. 16 Two parts of magnesium aluminum hydrotalcite containing CO3·4H2O were used to impart an auxiliary trapping effect on acidic components in functional particle region 4, and the rest were the same as in Example 1.
[0080] Comparative Example 1: Ordinary polytetrafluoroethylene membrane needle-punched felt filter material, the dust-facing surface 5 does not have functional particle zone 4, and S3 and S4 are not used, the rest is the same as in Example 1, as the benchmark for no functional particle zone 4.
[0081] Comparative Example 2: The difference from Example 1 is that S32 adopts an immersion coating method, increases the solid content of the liquid material, and does not apply negative pressure suction, so that the liquid material forms a continuous closed film layer on the dust-facing surface 5, and adjusts the remaining surface load after drying to be consistent with Example 1, in order to compare the difference between hole edge confinement and full coating clogging.
[0082] Comparative Example 3: The difference from Example 1 is that the catalyst is a manganese-cerium composite oxide without tungsten doping, with a manganese-cerium molar ratio of 6:4, used to control the sulfur and water resistance of tungsten.
[0083] Comparative Example 4: The difference from Example 1 is that an equal amount of conductive carbon black was used instead of antimony-doped tin dioxide to compare the durability of the antistatic component in an oxidizing atmosphere.
[0084] Comparative Example 5: The difference from Example 1 is that S31 does not contain the ethanol hydrolysate of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, and no fluorinated hydrophobic phase is formed on the dust-receiving surface, which is used as a control for anti-clogging bag effect.
[0085] Comparative Example 6: The difference from Example 1 is that the S2 plasma activation is omitted, and a polyurethane organic adhesive is used instead of a silicon-containing bound phase to fix the functional particles, which is used to compare the acid and heat resistance of the adhesive-free silicon-containing bound phase.
[0086] Comparative Example 7: The difference from Example 1 is that in S32, no negative pressure suction was applied and no fluorocarbon surfactant was added to adjust the surface tension. The surface tension of the liquid was about 30 mN / m. It was used to compare the effect of negative pressure and surface tension control on the morphology of the pore edge confinement.
[0087] Comparative Example 8: The difference from Example 1 is that the highest temperature range of the S6 gradient heat setting is 340°C, which is higher than the melting point of polytetrafluoroethylene, and is used to compare the effect of heat setting temperature on the membrane pore structure.
[0088] Comparative Example 9: The difference from Example 1 is that the S82 pinhole sealing is omitted and ordinary sewing is used to compare the effect of suture pinhole sealing on leakage.
[0089] Experimental Example 1: Filter media obtained from Examples 1 to 4, and Comparative Examples 1, 2, 7, and 8 were used. Air permeability was measured, and the air permeability retention rate was calculated as the ratio of the air permeability of the functional particle zone 4 to that of the base membrane. The initial filtration pressure difference was measured at a filtration velocity of 1 m / min. The filtration efficiency for 2.5 μm particles was determined by gravimetric method. The proportion of the projected area of the functional particle zone 4 to the dust-facing surface 5 was statistically analyzed using scanning electron microscopy. The average pore size was determined by bubble point method, and the average pore size retention rate was calculated. The components and key process parameters of each example and comparative example are listed in Table 1, and the data obtained in this experimental example are listed in Table 2. Figure 1 express.
[0090] Table 1. Components and key process parameters for each embodiment and comparative example:
[0091]
[0092] From Table 2 and Figure 1 As can be seen from the data, the initial filtration pressure difference reflects the operating resistance, the air permeability retention rate and the average pore size retention rate reflect the degree of openness of the membrane pore throat 6, and the proportion of projected area reflects the degree of discrete coverage of the functional particle region 4 on the dust-facing surface 5. Figure 1The initial filtration pressure difference is represented by the column height, and the air permeability retention rate is represented by the broken line. The initial filtration pressure difference of Examples 1 to 4 was 400 Pa to 480 Pa, the air permeability retention rate was 74% to 90%, and the average pore size retention rate was not less than 88%. In Comparative Example 2, which had the same areal load as Example 1, the projected area ratio increased to 95% due to the continuous closed membrane layer, the average pore size retention rate decreased to 55%, the initial filtration pressure difference increased to 760 Pa, and the air permeability retention rate decreased to 41%. In Comparative Example 7, the particles spread out without applying negative pressure or adjusting the surface tension, and the projected area ratio and pressure difference were in the middle. In Comparative Example 8, the average pore size retention rate decreased to 50% and the initial filtration pressure difference increased to 690 Pa because the highest temperature zone of heat setting was higher than the melting point of polytetrafluoroethylene. Therefore, under the same areal load, the pore edge confined functional particle region 4 formed by negative pressure suction combined with slit extrusion coating in step S32 of the present invention has a significantly lower operating resistance than the fully coated continuous membrane layer, and the air permeability retention rate decreases slowly with the increase of areal load. This shows that the present invention can maintain a low filtration resistance while introducing a higher functional load.
[0093] Table 2. Data on air permeability, pressure difference, filtration efficiency, and pore structure:
[0094]
[0095] Functional particles are fixed to the membrane pore edges and node protrusions by a silicon-containing bonding phase without forming a continuous membrane layer. The through-hole throats 6 between adjacent particles remain open, and the airflow passes through the membrane layer through the open throats. Therefore, the mutual constraint between the load and the filtration resistance is resolved. The pore size collapse of Comparative Example 8 is caused by the heat setting temperature being higher than the melting point of polytetrafluoroethylene, which causes the microporous structure to fuse together. This shows that controlling the temperature below the melting point in steps S5 and S6 of the present invention is necessary to preserve the pores.
[0096] Experimental Example 2: The filter media obtained from Examples 1 to 4 and Comparative Example 3 were used in a simulated flue gas fixed bed at a volume fraction of 500 × 10⁻⁶. -6 The removal rate of nitrogen oxides was determined by mixing nitric oxide, equimolar amounts of ammonia, and 5% (v / v) oxygen at temperatures ranging from 100°C to 300°C. The concentration of nitrogen oxides was determined by non-dispersive infrared absorption spectrometry. Then, a solution of 500 × 10⁻⁶ (v / v) oxygen was introduced at 210°C. -6 The removal rate of sulfur dioxide and 8% (v / v) water vapor was continuously measured for 24 hours. The obtained data are listed in Table 3, and are presented in the table below. Figure 2 express, Figure 2 In figure (a), the removal rate varies with temperature. Figure 2 (b) shows the curve of the removal rate of sulfur dioxide and water vapor as a function of time.
[0097] Table 3, Nitrogen oxide removal rate:
[0098]
[0099] From Table 3 and Figure 2 As can be seen, the removal rate at 180℃ to 240℃ reflects the catalytic activity and temperature window, while the removal rate after introducing sulfur dioxide and water vapor reflects the sulfur and water resistance. Figure 2 (a) The temperature response of tungsten-containing and tungsten-free catalysts is compared with the curves of Examples 1, 3, 4 and Comparative Example 3. Figure 2 (b) Compare the activity decay after sulfur and water treatment using the same curves for the four examples. Examples 1, 3, and 4, which contain tungsten, had a removal rate of 89% to 93% at 210°C and 85% to 89% after 24 hours of sulfur and water treatment. Example 2, which uses the lower limit of the parameters, still reached 80% at 210°C, while Comparative Example 3, which does not contain tungsten, had a removal rate of 86% at 210°C, which decreased to 70% at 240°C and further decreased to 58% after 24 hours of sulfur and water treatment.
[0100] In this invention, a tungsten-modified manganese-cerium composite oxide is used in functional particle region 4. Within the range of component parts and molar ratios covered, nitrogen oxides can be catalytically removed at medium and low temperatures. Tungsten provides acidic sites on the catalyst surface, inhibiting the deposition of ammonium sulfate on the active sites of manganese-cerium and alleviating the competitive adsorption of water vapor. Therefore, the activity remains significantly better than that without tungsten after sulfur and water passage. This anti-sulfur and anti-water effect is not a simple superposition of the individual effects of manganese-cerium and tungsten, but rather the protective effect of tungsten on the active sites, which originates from the inhibition of ammonium salt deposition by the acidic sites.
[0101] Experimental Example 3: Filter media obtained from Examples 1, 2, and 3, as well as Comparative Examples 1, 4, and 5, were used. Surface resistivity was measured, and the media were aged at 210°C for 24 hours in an acidic atmosphere with 8% oxygen (by volume) before being re-measured. The contact angle between water and n-hexadecane was measured using the seat drop method. Filtration and pulse cleaning cycles were performed under conditions of 80% relative humidity and the presence of ammonium bisulfate. The pressure differential recovery rate after cleaning and the pressure differential increase rate after 2 hours of operation were measured. The obtained data are listed in Table 4, and are presented in the table below. Figure 3 express, Figure 3 In Figure (a), the surface resistivity changes with oxidation aging time. Figure 3 (b) shows the curve of the filtration pressure difference changing with operating time under high humidity and ammonium bisulfate conditions.
[0102] Table 4. Antistatic, hydrophobic, oleophobic, and anti-clogging properties:
[0103]
[0104] From Table 4 and Figure 3 As can be seen, surface resistance and its value after aging reflect antistatic durability, contact angle reflects hydrophobicity and oleophobicity, and differential pressure recovery rate and differential pressure increase rate reflect anti-clogging and dust removal regeneration properties. Figure 3(a) Comparison of the resistivity changes of antimony-doped tin dioxide and carbon black during oxidative aging using curves from Examples 1, 3, and 4. Figure 3 (b) Comparison of the filtration pressure difference increments of Example 1, Comparative Example 5, and Comparative Example 1 with and without the fluorinated hydrophobic phase. The surface resistivity of Examples 1 to 3 containing antimony-doped tin dioxide was 10 Ω·cm. 6 Ω to 10 9 Ω, after 24 hours of aging, remained in the same order of magnitude, while the initial value of Comparative Example 4, which was replaced with carbon black, was 4 × 10. 7 Ω, increases to 3×10 after aging 11 Ω loses conductivity; comparative example 5, without a fluorinated hydrophobic phase, has a lower contact angle, a pressure recovery rate reduced to 68%, and a pressure drop rate increased to 12 Pa·min. -1 .
[0105] In step S31 of this invention, antimony-doped tin dioxide is used as the antistatic component, which can maintain its antistatic effect for a long time in an oxidizing acidic atmosphere, verifying the feasibility of this antistatic component. Antimony-doped tin dioxide is an inorganic n-type semiconductor and is not oxidized or ablated in an oxygen-containing atmosphere, while carbon black is oxidized and consumed under the same conditions, resulting in a sharp increase in resistance. The fluorinated hydrophobic phase, due to the perfluoroalkyl group, gives the dust-collecting surface a low surface energy, reducing the adhesion of sticky dust, thus resulting in a higher pressure differential recovery rate and a lower rate of increase in operating pressure differential after dust removal.
[0106] Experimental Example 4: The filter media obtained from Examples 1 to 4, as well as Comparative Examples 2 and 6, were used to determine the peel strength between the membrane and the needle-punched felt. After aging in an acidic atmosphere at 200°C for 72 hours, the peel strength was retested to calculate the retention rate. The functional point detachment rate was calculated based on the elemental retention before and after pulse backflushing, while simultaneously following the relationship described in step S33 of this invention. Based on the set non-volatile solids content Material supply flow rate Width With the linear speed of the conveyor belt The retained surface load was calculated, and the measured value was determined by weighing. The relative error was calculated by dividing the difference between the calculated value and the measured value by the calculated value. The obtained data are listed in Table 5, and are presented in the table below. Figure 4 express, Figure 4 (a) shows a comparison between peel strength and functional point detachment rate. Figure 4 (b) shows the comparison between the calculated and measured values of the retained surface load.
[0107] Table 5, Verification of the formula for interface robustness and retained surface load:
[0108]
[0109] From Table 5 and Figure 4As can be seen, the peel strength and its retention rate after acid heat aging reflect the bonding strength between the film and the felt, the functional point detachment rate reflects the adhesion strength of the functional particles, and the difference between the calculated and measured values of the retained surface load reflects the process controllability. Figure 4 (a) Peel strength and functional point detachment rate under three conditions: silicon-containing binder phase, full coating, and organic adhesive, using columnar and scatter plots as comparisons of Example 1, Comparative Example 2, and Comparative Example 6; Figure 4 (b) Comparison of the calculated and measured values of the retained surface load using scattered points from Examples 1 to 4. Examples 1 to 4, bonded with a silicon-containing binder, showed a peel strength retention rate of 75% to 77% and a functional point detachment rate of 6.5% to 8% after acid heat aging. Comparative Example 6, bonded with an organic adhesive, showed a retention rate reduced to 36% after acid heat aging, and Comparative Example 2, with full coating, showed a detachment rate of 22%. The relative error between the measured and calculated values of the retained surface load in Examples 1 to 4 was no greater than 3.5%. Therefore, it can be concluded that the present invention, based on activation in step S2, uses a silicon-containing binder to bond functional particles, resulting in superior bonding strength under acid heat conditions compared to organic adhesives. Furthermore, the surface load control formula described in step S33 of the present invention allows for accurate adjustment of the retained surface load. The silicon-containing binder is an acid- and heat-resistant silicon-oxygen network, while the organic adhesive degrades under acid heat, resulting in a low retention rate. The retained surface load is numerically equal to the mass flow rate of the non-volatile solids divided by the coated area, and therefore can be quantitatively adjusted by the feed flow rate and the conveyor belt speed.
[0110] Experimental Example 5: Using Example 4 and Example 1 as controls for auxiliary deacidification, the capture rate of acidic components was measured in simulated flue gas containing hydrogen chloride and hydrogen fluoride. Using Example 1 and Comparative Example 9 as controls for pinhole sealing, the leakage rate of the suture pinholes was measured by applying pressure to the suture section. The obtained data are listed in Table 6.
[0111] Table 6. Effects of assisted deacidification and pinhole sealing:
[0112]
[0113] As shown in Table 6, the capture rates of hydrogen chloride and hydrogen fluoride reflect the auxiliary deacidification effect, while the suture pinhole leakage rate reflects the pinhole sealing effect. Example 4, containing magnesium aluminum hydrotalcite, achieved capture rates of 45% and 40% for hydrogen chloride and hydrogen fluoride, respectively, significantly higher than the 8% and 6% of Example 1, which did not contain magnesium aluminum hydrotalcite. Example 1, sealed with fluorinated ethylene propylene copolymer, had a suture pinhole leakage rate of 0.3%, significantly lower than the 3.5% of the conventionally sewn Comparative Example 9. Therefore, it can be concluded that adding magnesium aluminum hydrotalcite in step S31 provides an auxiliary deacidification effect, and sealing with fluorinated ethylene propylene copolymer in step S82 reduces pinhole leakage. The alkaline sites of the magnesium aluminum hydrotalcite layer neutralize and capture acidic components. The melting point of fluorinated ethylene propylene copolymer is lower than that of polytetrafluoroethylene, allowing it to melt and fill pinholes at temperatures below the membrane melting point without damaging the microporous membrane.
[0114] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A dust collector bag made of PTFE-coated needle-punched felt filter media, characterized in that, The dust collector bag comprises a bag-shaped hollow filter body surrounded by PTFE membrane needle-punched felt filter media; wherein: The PTFE-coated needle-punched felt filter media includes polytetrafluoroethylene needle-punched felt and expanded polytetrafluoroethylene microporous membrane disposed on the dust-facing side of the polytetrafluoroethylene needle-punched felt. The side of the expanded polytetrafluoroethylene microporous membrane facing away from the polytetrafluoroethylene needle-punched felt is the dust-facing side. The other side of the expanded polytetrafluoroethylene microporous membrane is embedded in the gaps between the surface fibers of the polytetrafluoroethylene needle-punched felt to form a membrane-fiber interlocking interface. The dust-facing side has discretely distributed functional particle regions. The functional particle regions are fixed to the membrane pore edges and node protrusions of the expanded polytetrafluoroethylene microporous membrane by a silicon-containing bonding phase. The functional particle regions do not form a continuous closed membrane layer, and the through pore throats of the expanded polytetrafluoroethylene microporous membrane remain open. The functional particle zone is formed by drying and heat setting of a multifunctional liquid. Based on the mass fraction of non-volatile components in the multifunctional liquid, the multifunctional liquid includes 5-12 parts of tungsten-modified manganese-cerium composite oxide, 0.5-3 parts of antimony-doped tin dioxide, 0.5-3 parts of γ-glycidyl etheroxypropyltrimethoxysilane, and 0.2-1.5 parts of 1H,1H,2H,2H-perfluorodecyltriethoxysilane. The γ-glycidyl etheroxypropyltrimethoxysilane is hydrolyzed and condensed to form a silicon-containing phase, and the 1H,1H,2H,2H-perfluorodecyltriethoxysilane is hydrolyzed and condensed to form a fluorinated hydrophobic phase located on the dust-facing surface of the functional particle zone.
2. The PTFE-coated needle-punched felt filter bag according to claim 1, characterized in that, The tungsten-modified manganese-cerium composite oxide has a molar ratio of manganese, cerium, and tungsten of (5-7):(3-5):(0.5-1.5) based on the molar number of metal elements; the median particle size of the tungsten-modified manganese-cerium composite oxide is 0.05-0.20 μm, and the particle size corresponding to 90% of the cumulative volume distribution is not greater than 0.30 μm.
3. The PTFE-coated needle-punched felt filter bag according to claim 1, characterized in that, The antimony-doped tin dioxide contains 8%–12% antimony by mass, and has a number-average primary particle size of 20–30 nm; the polytetrafluoroethylene needle-punched felt has a surface density of 500–800 g / m³. 2 The expanded polytetrafluoroethylene microporous membrane has an average pore size of 0.2–0.5 μm, a porosity of 80%–90%, and an areal density of 5–15 g / m³. 2 .
4. The PTFE-coated needle-punched felt filter bag according to claim 1, characterized in that, The functional particle region also includes 0.2 to 1 part by weight of perfluorosulfonic acid resin, and 1 to 3 parts by weight of magnesium aluminum hydrotalcite and / or magnesium aluminum composite oxide.
5. A method for preparing a dust collector bag made of PTFE-coated needle-punched felt filter media as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S1. The pre-made polytetrafluoroethylene needle-punched felt is dried and subjected to tension constraint thermal stabilization treatment to obtain pre-stabilized polytetrafluoroethylene needle-punched felt. S2. The dust-facing surface of the expanded polytetrafluoroethylene microporous membrane is activated by atmospheric pressure dielectric barrier discharge plasma to obtain a surface-activated expanded polytetrafluoroethylene microporous membrane. S3. A multifunctional liquid containing tungsten-modified manganese-cerium composite oxide, antimony-doped tin dioxide, γ-glycidyl etheroxypropyltrimethoxysilane and 1H,1H,2H,2H-perfluorodecyltriethoxysilane is coated onto the dust-facing surface activated in step S2. A negative pressure is applied to the back of the expanded polytetrafluoroethylene microporous membrane to cause the solid particles in the multifunctional liquid to adhere to the pore edges and node protrusions of the membrane pores, forming discretely distributed functional particle regions. The functional particle regions do not form a continuous closed membrane layer, and the through-hole throats of the expanded polytetrafluoroethylene microporous membrane remain open. S4. The coated expanded polytetrafluoroethylene microporous membrane is pre-dried by infrared radiation. S5. The expanded polytetrafluoroethylene microporous membrane treated in step S4 is stacked with the pre-stabilized polytetrafluoroethylene needle-punched felt on its uncoated side and hot-pressed to form a membrane-fiber interlocking interface, with the dust-facing side coated with the functional particle area facing outward. S6. The hot-pressed filter material is subjected to gradient heat setting to obtain PTFE membrane needle-punched felt filter material; S7. Perform pulsed airflow pre-purging treatment on the PTFE-coated needle-punched felt filter material to remove weakly attached particles in the functional particle area; S8. The filter material treated in step S7 is sewn together to form a bag-shaped hollow filter body, thus obtaining the PTFE-coated needle-punched felt filter material dust collector bag.
6. The preparation method according to claim 5, characterized in that, Step S1 includes: S11. After degreasing and dust removal, the pre-made polytetrafluoroethylene needle-punched felt is dried at 100-120℃ to constant weight. S12. The dried polytetrafluoroethylene needle-punched felt is heat-stabilized at 200-240℃ for 5-20 minutes under tension constraint to obtain pre-stabilized polytetrafluoroethylene needle-punched felt. Step S2 includes: S21. Position the dust-facing side of the expanded polytetrafluoroethylene microporous membrane directly against the dielectric barrier discharge electrode. S22, at atmospheric pressure with an energy density of 0.5–3 W·min / cm³ 2 The dust-facing surface is activated by dielectric barrier discharge plasma to obtain a surface-activated expanded polytetrafluoroethylene microporous membrane.
7. The preparation method according to claim 5, characterized in that, The preparation of the multifunctional liquid in step S3 includes: S31. Tungsten-modified manganese-cerium composite oxide with a median volumetric particle size of 0.05–0.20 μm and a particle size not greater than 0.30 μm corresponding to 90% volumetric cumulative distribution, antimony-doped tin dioxide with a number-average primary particle size of 20–30 nm, hydrolysate of γ-glycidyl etheroxypropyltrimethoxysilane, and ethanol hydrolysate of 1H,1H,2H,2H-perfluorodecyltriethoxysilane are added to a mixed solvent of deionized water and isopropanol at a volume ratio of 6:
4. The mixture is ultrasonically dispersed for 30–60 min, and then a fluorocarbon surfactant is added to adjust the surface tension of the multifunctional liquid to 18–22 mN / m. The multifunctional liquid is dried at 105 °C to constant weight and the non-volatile solids content is measured to be 0.04–0.10 g / mL. Perfluorosulfonic acid resin and magnesium aluminum hydrotalcite and / or magnesium aluminum composite oxide are added to the mixed solvent.
8. The preparation method according to claim 5, characterized in that, The coating and negative pressure suction in step S3 include: S32. The multifunctional liquid is coated onto the dust-facing surface activated in step S2 using slit extrusion coating, and a negative pressure of -2 to -8 kPa is applied to the back of the expanded polytetrafluoroethylene microporous membrane to draw in solid particles in the multifunctional liquid, so that the solid particles in the liquid are fixed at the pore edges and node protrusions of the membrane pores to form discretely distributed functional particle regions, while the through pore throats of the expanded polytetrafluoroethylene microporous membrane remain open. S33. During the coating process in step S32, adjust the remaining surface load after drying according to the following formula: ; In the formula, To retain surface load after drying; The content of non-volatile solids in the multifunctional liquid is measured after drying at 105°C to constant weight. The feed flow rate for the slit extrusion nozzle; The width of the expanded polytetrafluoroethylene microporous membrane; The linear speed of the conveyor belt of the expanded polytetrafluoroethylene microporous membrane; and by adjusting , , , The intensity of the negative pressure suction ensures that the projected area of the functional particle region on the dust-facing surface accounts for 5% to 35%, and the surface load retained after drying is 1 to 6 g / m². 2 .
9. The preparation method according to claim 5, characterized in that, Step S4 involves pre-drying the coated expanded polytetrafluoroethylene microporous membrane using infrared technology at a membrane surface temperature of 80–140°C for 5–30 seconds; Step S5 includes: S51. The expanded polytetrafluoroethylene microporous membrane treated in step S4 is stacked with the pre-stabilized polytetrafluoroethylene needle-punched felt with its uncoated side facing outwards. S52. Using a hot press roller, hot press for 5-30 seconds at 280-320℃ and 0.05-0.5MPa, the uncoated side of the expanded polytetrafluoroethylene microporous membrane is hot-pressed and deformed, and pressed into the gaps between the surface fibers of the polytetrafluoroethylene needle-punched felt to form a membrane-fiber interlocking interface.
10. The preparation method according to claim 5, characterized in that, Step S6 involves: subjecting the hot-pressed filter material to gradient heat setting at three temperature zones (200℃, 260℃, and 300℃) under tension constraint, with a total residence time of 1–5 minutes, to obtain PTFE-coated needle-punched felt filter material; Step S8 further includes: S82. Apply a fluorinated ethylene propylene copolymer dispersion along the suture pinhole area of the bag-shaped hollow filter body, and locally hot-press at 260-290°C to melt the fluorinated ethylene propylene copolymer and seal the pinhole.
Citation Information
Patent Citations
Polytetrafluoroethylene fiber with antistatic function of and preparation method thereof
CN101985783A
Antistatic PTFE fiber and needled felt with same
CN113969431A